Dynamics of soft nanoparticle suspensions at hard X-ray FEL sources below the radiation-damage threshold. (2018) - Lehmkuhler, Felix; Valerio, Joana; Sheyfer, Dina; Roseker, Wojciech; Schroer, Martin A.; Fischer, Birgit
No abstract available